2003
DOI: 10.1093/molbev/msg058
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Recombination of mtDNA in the Marine Mussel Mytilus trossulus from the Baltic

Abstract: A number of studies have claimed that recombination occurs in animal mtDNA, although this evidence is controversial. Ladoukakis and Zouros (2001) provided strong evidence for mtDNA recombination in the COIII gene in gonadal tissue in the marine mussel Mytilus galloprovincialis from the Black Sea. The recombinant molecules they reported had not however become established in the population from which experimental animals were sampled. In the present study, we provide further evidence of the generality of mtDNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
101
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 21 publications
4
101
1
6
Order By: Relevance
“…Overall, these studies have shown (i) a high level of nucleotide sequence divergence but nearly identical gene content between F and M genomes within each species, (ii) an accelerated rate of molecular evolution of both the M and the F genomes compared to other animal mitochondrial genomes, (iii) an accelerated rate of molecular evolution of M genomes compared to F genomes, (iv) an absence of atp8 in mytiloid mussels, (v) the presence of a second trnM (i.e., transfer RNA gene for methionine) in mytiloid and veneroid bivalves, (vi) recombination between M and F genomes in mytiloid mussels, (vii) periodic ''role reversals'' (masculinization) of female-transmitted mtDNA in mytiloid mussels that are subsequently transmitted through sperm, (viii) different gene order between F and M genomes in unionoids, and (ix) the presence of a unique extension of the cytochrome c oxidase subunit II gene in the M (but not the F) genome in unionoids (reviewed in Breton et al 2007; see also Chapman et al 2008). An important hypothesis that has emerged from sequencing studies of species with DUI is that genderspecific sequences and/or sequences that exhibit the highest level of nucleotide divergence between the F and M genomes (i.e., regions that are under different, potentially gender-specific selective constraints and could, therefore, have different roles in either genome) are the most likely candidates for determining whether a mitochondrial genome will be transmitted maternally or paternally (Zouros 2000;Burzyń ski et al 2003;Cao et al 2004a;Breton et al 2006Breton et al , 2007Theologidis et al 2007;Venetis et al 2007;Cao et al 2009). For example, it has been demonstrated in marine mussels that masculinized type genomes (i.e., an F genome that ''masculinizes'' and takes on the role of the previous M genome) are essentially recombinants composed of an F genome's coding and control regions, with an additional standard M-type control region (Burzyń ski et al 2003;Breton et al 2006;Venetis et al 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, these studies have shown (i) a high level of nucleotide sequence divergence but nearly identical gene content between F and M genomes within each species, (ii) an accelerated rate of molecular evolution of both the M and the F genomes compared to other animal mitochondrial genomes, (iii) an accelerated rate of molecular evolution of M genomes compared to F genomes, (iv) an absence of atp8 in mytiloid mussels, (v) the presence of a second trnM (i.e., transfer RNA gene for methionine) in mytiloid and veneroid bivalves, (vi) recombination between M and F genomes in mytiloid mussels, (vii) periodic ''role reversals'' (masculinization) of female-transmitted mtDNA in mytiloid mussels that are subsequently transmitted through sperm, (viii) different gene order between F and M genomes in unionoids, and (ix) the presence of a unique extension of the cytochrome c oxidase subunit II gene in the M (but not the F) genome in unionoids (reviewed in Breton et al 2007; see also Chapman et al 2008). An important hypothesis that has emerged from sequencing studies of species with DUI is that genderspecific sequences and/or sequences that exhibit the highest level of nucleotide divergence between the F and M genomes (i.e., regions that are under different, potentially gender-specific selective constraints and could, therefore, have different roles in either genome) are the most likely candidates for determining whether a mitochondrial genome will be transmitted maternally or paternally (Zouros 2000;Burzyń ski et al 2003;Cao et al 2004a;Breton et al 2006Breton et al , 2007Theologidis et al 2007;Venetis et al 2007;Cao et al 2009). For example, it has been demonstrated in marine mussels that masculinized type genomes (i.e., an F genome that ''masculinizes'' and takes on the role of the previous M genome) are essentially recombinants composed of an F genome's coding and control regions, with an additional standard M-type control region (Burzyń ski et al 2003;Breton et al 2006;Venetis et al 2007).…”
mentioning
confidence: 99%
“…An important hypothesis that has emerged from sequencing studies of species with DUI is that genderspecific sequences and/or sequences that exhibit the highest level of nucleotide divergence between the F and M genomes (i.e., regions that are under different, potentially gender-specific selective constraints and could, therefore, have different roles in either genome) are the most likely candidates for determining whether a mitochondrial genome will be transmitted maternally or paternally (Zouros 2000;Burzyń ski et al 2003;Cao et al 2004a;Breton et al 2006Breton et al , 2007Theologidis et al 2007;Venetis et al 2007;Cao et al 2009). For example, it has been demonstrated in marine mussels that masculinized type genomes (i.e., an F genome that ''masculinizes'' and takes on the role of the previous M genome) are essentially recombinants composed of an F genome's coding and control regions, with an additional standard M-type control region (Burzyń ski et al 2003;Breton et al 2006;Venetis et al 2007). This has led to the proposition that an M-type control region, particularly its most variable domain called VD1 by Cao et al (2004a), might be necessary to confer the paternal role on genomes that are otherwise F-like (Burzyń ski et al 2003;Breton et al 2006;Venetis et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Till 2000 it was believed that, contrary to nuclear DNA, mtDNA did not undergo recombination. However recently, the body of evidence supporting this phenomenon in animal mtDNA has been increasing (LADOUKAKIS & ZOUROS 2001, PIGANEAU et al 2004, SHAO et al 2005, TSAOUSIS et al 2005, CIBOROWSKI et al 2007), including marine bivalves (LADOUKAKIS & ZOUROS 2001, BURZYÑSKI et al 2003.…”
Section: Malacologica Issn 1506-7629mentioning
confidence: 99%
“…The frequency of heteroplasmy in M. trossulus from the Gulf of Gdañsk, Poland is 32.7% of males and 3.5% of females, and the phenomenon is not a result of hybridisation (WENNE 1993). In the case of marine bivalves there is also evidence for recombination, and reversal or masculinisation events between these molecules of mtDNA, hence in phylogenetic analyses the two mtDNA molecules may not form separate clades (HOEH et al 1996b, 2002a, QUESADA et al 1999, BURZYÑSKI et al 2003, BRETON et al 2007.…”
Section: Malacologica Issn 1506-7629mentioning
confidence: 99%